Resistance training using low cost elastic tubing is equally effective to conventional weight machines in middle-aged to older healthy adults: A quasi-randomized controlled clinical trial - de Lima, Fabiano Francisco [UNESP]; Camillo, Carlos Augusto; Gobbo, Luis Alberto [UNESP]; Trevisan, Iara Buriola [UNESP]; do Nascimento, Wesley B. B. M. [UNESP]; Silva, Bruna Spolador de Alencar [UNESP]; Lima, Manoel Carlos Spiguel [UNESP]; Ramos, Dionei [UNESP]; Ramos, Ercy M. C. [UNESP] (My University, 2018)
The objectives of the study were to compare the effects of resistance training using either a low cost and portable elastic tubing or conventional weight machines on muscle force, functional exercise capacity, and health-related quality of life (HRQOL) in middle-aged to older healthy adults. In this clinical trial twenty-nine middle-aged to older healthy adults were randomly assigned to one of the three groups a priori defined: resistance training with elastic tubing (ETG; n = 10), conventional resistance training (weight machines) (CTG; n = 9) and control group (CG, n = 10). Both ETG and CTG followed a 12-week resistance training (3x/week - upper and lower limbs). Muscle force, functional exercise capacity and HRQOL were evaluated at baseline, 6 and 12 weeks. CG underwent the three evaluations with no formal intervention or activity counseling provided. ETG and CTG increased similarly and significantly muscle force (∆16-44% in ETG and ∆25-46% in CTG, p < 0.05 for both), functional exercise capacity (ETG ∆4 ± 4% and CTG ∆6±8%; p < 0.05 for both). Improvement on pain domain of HRQOL could only be observed in the CTG (∆21 ± 26% p = 0.037). CG showed no statistical improvement in any of the variables investigated. Resistance training using elastic tubing (a low cost and portable tool) and conventional resistance training using weight machines promoted similar positive effects on peripheral muscle force and functional exercise capacity in middle-aged to older healthy adults.
Keywords: Exercise; Functional exercise capacity; Muscle strength